Bending properties of the multilayer‐connected biaxial weft knitted fabrics‐reinforced composites made with carbon fibers. Issue 12 (5th July 2014) - Qi, Yexiong; Li, Jialu; Liu, Liangsen
Abstract : This article presents an experimental study of bending properties of multilayer‐connected biaxial weft knitted (MBWK) fabrics‐reinforced composites made with carbon fibers. Three types of composites are used in bending test, which are three‐layer‐connected biaxial weft knitted fabric‐reinforced composite, four‐layer‐connected biaxial weft knitted fabric‐reinforced composite and five‐layer‐connected biaxial weft knitted fabric‐reinforced composite. Two‐way ANOVA analyzing method was used to deal with whether the carbon fiber volume fraction and the cutting direction have significant effect on the bending strength of the MBWK fabrics‐reinforced composites. Failure analysis is also available by means of samples debris examination to identify the failure mode. POLYM. COMPOS., 36:2291–2302, 2015. © 2014 Society of Plastics Engineers